1970
DOI: 10.1021/ja00712a049
|View full text |Cite
|
Sign up to set email alerts
|

Polypeptides. XLIV. Potent synthetic S-peptide antagonists

Abstract: does not appear to be of a type which can account for enzymic catalysis. ConclusionSince most enzymic reactions in which thiamine pyrophosphate is a cofactor are mechanistically similar to the pyruvate decarboxylase reaction,47 our results and the above discussion are relevant to many thiamine pyrophosphate-dependent enzymic reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1970
1970
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…The interaction has been studied in experiments based on reconstitution of S-peptide and chemically synthesized analogs of S-peptide with S-protein (Hofmann et al 1970;Marchiori et al 1972). It is of major interest to determine whether or not the Glu-2 9 9 9 Arg-10 + ion pair is present in the C-peptide helix, both because of its unusual nature (formed between residues that are spaced eight residues apart) and because it fixes the amino-terminal boundary of the helix between Glu-2 and Thr-3.…”
Section: Interaction Of the Helix Dipole With Charged Groupsmentioning
confidence: 99%
“…The interaction has been studied in experiments based on reconstitution of S-peptide and chemically synthesized analogs of S-peptide with S-protein (Hofmann et al 1970;Marchiori et al 1972). It is of major interest to determine whether or not the Glu-2 9 9 9 Arg-10 + ion pair is present in the C-peptide helix, both because of its unusual nature (formed between residues that are spaced eight residues apart) and because it fixes the amino-terminal boundary of the helix between Glu-2 and Thr-3.…”
Section: Interaction Of the Helix Dipole With Charged Groupsmentioning
confidence: 99%
“…Boc-5-0H (5) was transformed to Boc-5-0NSu (6) and H-5-0H (7), and these pentapeptides were then coupled to produce Boc-lO-OH (8). Compound 8 was converted to H-l O-ONSu' CF3COOH (10) and then treated with pyridine at a high dilution.…”
Section: Gramicidin S (Gs) Is a Cyclic Decapeptide Cyclo(-valmentioning
confidence: 99%
“…A solution of Boc-Pro-ONSu (l.37g, 4.4mmol)IO) in dioxane (20 ml) was then added, and the resulting mixture was stirred overnight at room temperature. The mixture was evaporated, the residue was triturated with 10% citric acid, and the solid was collected: yield, (8). To a solution of 7 (1.94 g, 2.2 mmol) and NEt 3 (0.66ml, 4.4 mmol) in DMF (20ml) was added a solution of 6 (1.76 g, 2 mmol) in DMF (20 ml) at ODe.…”
Section: Boc-pro-orn(z)-orn(for)-leu-o-phe-oh (5) Compound 4 (293 Gmentioning
confidence: 99%
“…In experiments by using ribonuclease S' as a analogues with substitutions at position 12. Investigations by Hofmann et al (1970) and by Dunn et al (1974) showed that replacement of the imidazolyl group (pKI -6) by the isosteric pyrazol-3-yl or 4fluoroimidazolyl moiety with a much lower pKa leaves unimpaired the capacity of binding to Sprotein, but results in an inactive ribonuclease S' complex. The data on the peptides with Hhi-12 and Nhi-12 prove that steric changes in the residue at position 12 may leave the function intact though the binding to S-protein is affected.…”
Section: Residue 12mentioning
confidence: 99%